Tatalaksana Pemeriksaan CT Scan Abdomen Dengan Kontras Dengan Klinis CA Recti - Irfan Irfan; Rahmat Widodo (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2024)
Abdominal CT scan examination aims to determine the pathology and anatomy of organs in the abdominal area in the form of crossectional support images produced after the scanning process (Nesseth R 2000). CA Recti can be seen during this examination process through contrast media. The use of contrast drugs in general aims to analyze the presence or absence of tissues that have a different amount of contrast absorption compared to surrounding tissues.